The Effect of e-WOM on Foreign Students’ Travel Intention Related to Visiting Tourism Destinations along Thailand’s Andaman Coast in the Wake of the COVID-19 Pandemic: Mediating Roles of Destination Image - Thaothampitak, Wipada; Wongsuwatt, Sippavit (Journal of Community Development Research (Humanities and Social Sciences); Vol 15 No 1 (2022): January - March 2022DO - 10.14456/jcdr-hs.2022.6, 2022)
Domestic tourism will play an important role in driving the economy of the country in the wake of the COVID-19 pandemic. This study aims to investigate the effect of e-WOM on travel intention and the mediating role of the destination’s image to determine if the COVID-19 pandemic has caused any changes to this well-established paradigm. Data was collected from two-hundred and eighty foreign students in Thailand using an online questionnaire. Structural equation modeling (SEM) was used to analyze the data and test the hypotheses related to the confirmatory factors. The foreign students saw Phuket Province as the most popular destination that they intended to visit and Google was the most online platform they used to obtain information about their intended destinations. Results from the SEM revealed positive relationships between e-WOM and travel intention, as well as the positive effect of destination image on travel intention. In addition, not only was the travel intention of the foreign students had influenced by e-WOM, it was also indirectly affected by the tourism destination’s image. In terms of implications, our findings would suggest that the COVID-19 pandemic has strengthened the power of e-WOM and Destination image affect travel intention and that online tourism public relations and destination image development should be enhance to increase domestic tourism along Thailand’s Andaman Coast, especially with regard to the target group of foreign students studying in Thailand. Keywords: e-WOM, Destination Image, Travel Intention, Foreign Students, Thailand’s Andaman Coast